Biosorption of molasses dyes by viable and non-viable microbial biomass - Barrera, Soledad (2011)
Molasses, a by-product of sugar extraction process, is a common raw material used in several industrial fermentations. However, molasses contains colored substances, some of them with inhibitory activities. Thus, innovative technologies, such as biosorption, are needed as alternatives to conventional methods to find inexpensive ways of removing dyes. With respect to dye biosorption, microbial biomass (bacteria, fungi, microalgae, etc.) outperformed macroscopic materials (sea-weeds, crab shell, etc.). The reason for this discrepancy is due to the nature of the cell wall constituents and functional groups involved in dye binding. In this connection, the major objective of this study was to investigate the potential of viable and non-viable microbial biomasses as biosorbent for the removal of dyes from sugar cane molasses. Materials and methods: Both viable and inactivated by autoclaving biomasses of Aspergillus niger ATCC MYA 135, Saccharomyces cerevisiae and Brevibacillus agri MIR E12 were used. Microorganisms were grown on agarized medium as well as in liquid medium. Potato glucose, LB and YEPD were used for the cultivation of A. niger, B. agri and S. cerevisiae, respectively. Decolorization experiments were conducted at 30 °C by shaking molasses solution at 300 rpm during 20 min in the presence of 1.5 or 3.0 % of microbial biomass (wet weight/v). The molasses pH was adjusted at 3, 7 or 9 being its initial reducing sugar concentration 10 g/l. Decolorization capacity was determined by monitoring the absorbance at 475 nm. Results and conclusions: The initial molasses pH value was an important factor for the biosorption process. In the primary screening step, the inactivated biomass of B. agri grown in liquid medium showed the highest decolorization capacity (47 %) when a molasses at pH 3 was used. Interestingly, the total amount of reducing sugar did not significantly change. In addition, the production of an extracellular lipase from B. agri was significantly increased when this treated molasses was used as carbon source. On the other hand, the best decolorization capacity obtained with either A. niger or S. cerevisiae was detected with viable biomass growing on agarized medium and using molasses at initial pH 9. These results show the ability of microbial biomass to remove colored substances from sugar cane molasses.